Extent of Water Adulteration and its Influence on Physical Characteristics of Market Milk - Shaikh, Nida; Soomro, Aijaz H.; Sheikh, Saghir A.; Khaskheli, Muhammad (Pakistan Journal of Nutrition, 2013)
The study was carried out to investigate the extent of water adulteration and its effect on the physical characteristics of market milk at the Institute of Food Sciences and Technology, Sindh Agriculture University, Tandojam. For this purpose, two different areas i.e., Hyderabad city (B) and its surrounding areas (C) were selected for sampling of market milk and from each area twenty samples were collected randomly from different sale points. Control milk samples (A) were also obtained from University dairy farm. The data revealed that all the samples of both areas were adulterated with water (100%). The extraneous water in the market milk of Hyderabad city remained 21.18% while in surrounding areas of Hyderabad it occurred 17.75%. The data regarding physical characteristics between control and market milk samples showed significant differences in pH value, freezing point, specific gravity, titratable acidity and viscosity. It is concluded from the present study that all the market milk samples did not meet the required quality accepted as standard.